Genome comparison of the epiphytic bacteria Erwinia billingiae and E. tasmaniensis with the pear pathogen E. pyrifoliae - Kube, Michael; Migdoll, Alexander M.; Gehring, Isabel; Heitmann, Katja; Mayer, Yvonne; Kuhl, Heiner; Knaust, Florian; Geider, Klaus; Reinhardt, Richard (BMC genomics, 2010)
The genus Erwinia includes plant-associated pathogenic and non-pathogenic Enterobacteria. Important pathogens such as Erwinia amylovora, the causative agent of fire blight and E. pyrifoliae causing bacterial shoot blight of pear in Asia belong to this genus. The species E. tasmaniensis and E. billingiae are epiphytic bacteria and may represent antagonists for biocontrol of fire blight. The presence of genes that are putatively involved in virulence in E. amylovora and E. pyrifoliae is of special interest for these species in consequence.
Gesehen am 07.03.2023